A method for preparing functional polyester fabric

By combining porous silk powder with nano TiO2 particles and sorting with polyester fabric, the problems of poor sweat conduction and unsightly warmth and beauty of polyester fabric are solved, and the effects of moisture absorption and heat generation and self-heating insulation are achieved, which improves the comfort and aesthetics of the clothing.

CN116556059BActive Publication Date: 2025-05-09WUJIANG DEYI FASHIONS CLOTHS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310454663.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-25
Publication Date
2025-05-09
Estimated Expiration
2043-04-25

AI Technical Summary

Technical Problem

Existing polyester fabrics are not easy to sweat when sweating, resulting in stuffy and discomfort. The traditional warmth method causes the clothing to be bloated and has no aesthetic feeling, and cannot meet the dual requirements of comfort and aesthetics.

Method used

By combining porous silk powder with nano TiO2 particles, silk/TiO2/polyaniline composite particles are prepared and added to the finishing solution, chemical etching and reducing treatment and impregnation and finishing of polyester fabrics are carried out to form polyester fabrics with moisture absorption and heating effect.

Benefits of technology

The moisture absorption and insulation effect of polyester fabric is achieved, and the binding force is enhanced by polyaniline coating, which has the effect of self-heating and heating heating, while improving the comfort and aesthetics of the clothing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for preparing a functional polyester fabric, comprising the following steps: S1. chemically etching and reducing the polyester fabric to obtain the treated polyester fabric; S2. adding a certain amount of porous silk powder to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, stirring sufficiently to allow the surface and interior of the porous silk fibers to fully adsorb the nano-TiO2 particles, filtering and drying to obtain composite particles; S3. adding the composite particles to a solvent, then adding aniline monomer to the composite particle solution, and ultrasonically dispersing until the solution is uniform; S4. successively adding hydrochloric acid and ammonium persulfate solution to the uniform solution prepared in step S3, washing, filtering and drying to obtain silk / TiO2 / polyaniline composite particles; S5. adding the composite particles prepared in step S4 and a crosslinking agent to a silk fibroin peptide solution to prepare a finishing liquid, directly immersing the polyester fabric treated in step S1 in the finishing liquid, and immersing to obtain a silk powder-modified polyester thermal insulation fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional fabrics, and in particular to a method for preparing functional polyester fabrics. Background Art

[0002] Polyester is the most industrialized and used synthetic fiber in the market. Compared with other natural or chemical fibers, polyester has stronger light resistance and wear resistance, higher elasticity and strength, and is therefore widely used in the field of clothing. Polyester has a weak moisture absorption capacity, with a moisture regain of only 0.4%. It is a typical hydrophobic material. Therefore, when people sweat, the sweat on the body surface is not easily conducted to the outside of the fabric through polyester, which makes people feel stuffy and uncomfortable. In order to improve the wearing performance of polyester, polyester is usually blended with other fibers such as cotton, viscose, acrylic, and spandex in industry. For winter clothing, the ability to keep warm is one of the important indicators to test its comfort. The traditional method of keeping warm is to prevent heat convection, control heat conduction, and reduce heat radiation. For example, it is achieved by accumulating thick fabrics or cotton wool for heat preservation, or coating the fabric with a metal coating for heat preservation. However, traditional warm clothing is too bulky and has no aesthetic appeal, which makes people inconvenient to move. As people's requirements for clothing increase, they gradually no longer meet people's needs. Moisture-absorbing and heat-generating fabrics meet people's requirements for both comfort and aesthetics in clothing, and therefore have great market prospects.

[0003] Mulberry silk is composed of two triangular or semi-elliptical silk fibers and outer sericin. Silk protein accounts for 70%-80% of the total silk fiber, and the components are composed of various amino acids such as tyrosine, alanine, and serine. Due to the hydrophilic groups in amino acids themselves, silk has good hygroscopicity, and the equilibrium regain under standard conditions can reach about 11%. Silk protein can improve the wrinkle resistance of viscose and silk, and improve the wearability of chemical fiber fabrics such as acrylic and polyester. In addition, silk protein is conducive to the dyeing of dyes on fabrics, and the color fastness of dyed fabrics is good, and no auxiliaries are required, which has little impact on the environment. At the same time, silk fiber has good elasticity and good biocompatibility, which is suitable for biological applications. Different forms can be obtained after different treatments, such as fibers, solutions, powders, and gels. Silk powder not only has the good hygroscopicity of silk protein itself, but also has the characteristics of large specific surface area of ​​powder. Therefore, adding silk powder to printing paste to regulate the structure of the coating film to improve the wearability of printed fabrics has good application value. Summary of the invention

[0004] Technical problem to be solved: The purpose of the present invention is to provide functional polyester fabrics, by combining modified silk powder and polyester fabrics, to obtain a polyester fabric with moisture absorption and heat generation effects.

[0005] Technical solution: A method for preparing a functional polyester fabric, comprising the following steps:

[0006] S1. The polyester fabric is heated in a water bath in a mixed solution of NaOH and ethylenediamine, and the polyester fabric is chemically etched and reduced to obtain a treated polyester fabric;

[0007] S2. A certain amount of porous silk powder was added to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, and the surface and interior of the porous silk fibers were fully adsorbed with nano-TiO2 particles, and the composite particles were filtered and dried;

[0008] S3. The composite particles are added to a solvent, and then the aniline monomer is added to the composite particle solution, and ultrasonically dispersed until the solution is uniform;

[0009] S4. Hydrochloric acid and ammonium persulfate solution were successively added to the homogeneous solution prepared in step S3, the reaction was stirred to obtain a black suspension, which was washed, filtered and dried to obtain silk / TiO2 / polyaniline composite particles;

[0010] S5. Add the composite particles and cross-linking agent prepared in step S4 to the silk peptide solution to prepare a finishing solution, and directly immerse the polyester fabric treated in step S1 in the finishing solution to obtain a silk powder-modified polyester thermal insulation fabric.

[0011] Preferably, in step S1, the concentration of NaOH is 1.5-2.5wt%, the concentration of ethylenediamine is 3-4wt%, the water bath temperature is 70-80°C, the treatment time is 1-2h, and the bath ratio is 1:50-100.

[0012] Preferably, the method for preparing the porous silk powder in step S2 comprises the following steps:

[0013] S11. The undegummed silk fibers are chopped into short silk fibers, and then the short silk fibers are mixed with water and ground, and finally the silk powder is collected by spray drying;

[0014] S12. Add the silk powder prepared in step S1 into water to prepare a silk suspension, subject the silk suspension to high-pressure homogenization to obtain a viscous slurry of porous silk powder liquid, and filter and dry to obtain porous silk powder.

[0015] Preferably, in step S11, the mass ratio of the silk staple fibers to water is 1:(5-10); the silk staple fibers and water are ground in a stirred ball mill for 2-6 h.

[0016] Preferably, the concentration of the silk suspension in step S12 is 6-10wt%, and the homogenization pressure is 60-80MPa.

[0017] Preferably, in step S2, the mass ratio of the porous silk powder to the nano-TiO2 particles is 10:4-7, the mass ratio of silk fibroin to sodium alginate is 2:1-2, and the concentration of the silk fibroin / sodium alginate viscous aqueous solution is 8-12wt%.

[0018] Preferably, in step S3, the mass ratio of the composite particles to the aniline monomer is 1:0.8-1.

[0019] Preferably, in step S5, the concentration of silk peptide in the finishing solution is 10-18 g / L, the concentration of the cross-linking agent is 15-20 g / L, the immersion is carried out at 80-90° C. for 30-50 min, and the bath ratio is 1:50-100.

[0020] Beneficial effects: The preparation method of the present invention has the following advantages:

[0021] The present invention combines porous silk protein with nano titanium dioxide particles with far-infrared heating to prepare a functional composite material, which is added to the finishing liquid, so that the composite particles with porous effect and far-infrared heating effect are adsorbed on the surface of the fabric, so that the fabric has both moisture absorption and heat preservation effects, and can also self-heat to achieve the effect of heating and heat preservation;

[0022] In the present invention, the silk is first crushed to obtain powder particles. At this time, the powder does not have a porous effect. A high-pressure homogenization treatment is used to obtain a silk powder with a porous effect. At this time, the powder can expose more active groups. The exposure of the active groups is conducive to moisture absorption. At the same time, the powder has a porous effect, which is conducive to the storage of air and achieves a heat preservation effect.

[0023] Nano titanium dioxide has the function of far-infrared heating, but in order to further store heat, the present invention attaches titanium dioxide to the interior and surface of silk powder. After heat generation, the heat is further stored inside the porous particles to prevent heat loss. However, the combination of titanium dioxide and silk is limited. Polyaniline is used to coat the surface of silk powder containing titanium dioxide to enhance the combination of the two. At the same time, after polyaniline coating, the fabric also has a certain electromagnetic shielding effect. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments:

[0025] Example 1

[0026] A method for preparing a functional polyester fabric comprises the following steps:

[0027] S1. The polyester fabric is heated in a water bath in a mixed solution of 1.5wt% NaOH and 4wt% ethylenediamine, the water bath temperature is 70°C, the treatment time is 2h, the bath ratio is 1:50, and the polyester fabric is subjected to chemical etching and reduction treatment to obtain a treated polyester fabric;

[0028] S2. A certain amount of porous silk powder was added to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, wherein the mass ratio of the porous silk powder to the nano-TiO2 particles was 10:4, the mass ratio of the silk fibroin to the sodium alginate was 2:1, and the concentration of the viscous aqueous solution of silk fibroin / sodium alginate was 12wt%, and the mixture was stirred sufficiently to allow the surface and interior of the porous silk fibers to fully adsorb the nano-TiO2 particles, and the composite particles were filtered and dried to obtain;

[0029] S3. The composite particles are added to a solvent, and then the aniline monomer is added to the composite particle solution, the mass ratio of the composite particles and the aniline monomer is 1:0.8, and ultrasonically dispersed until the solution is uniform;

[0030] S4. Hydrochloric acid and ammonium persulfate solution were successively added to the homogeneous solution prepared in step S3, the reaction was stirred to obtain a black suspension, which was washed, filtered and dried to obtain silk / TiO2 / polyaniline composite particles;

[0031] S5. Add the composite particles and cross-linking agent prepared in step S4 to the silk peptide solution to prepare a finishing solution, wherein the concentration of the silk peptide in the finishing solution is 10 g / L, and the concentration of the cross-linking agent is 15 g / L. Directly immerse the polyester fabric treated in step S1 in the finishing solution at 80°C for 50 min, with a bath ratio of 1:100, to obtain silk powder-modified polyester thermal insulation fabric.

[0032] The method for preparing the porous silk powder in step S2 comprises the following steps:

[0033] S11. The undegummed silk fibers were chopped into short silk fibers, and then the short silk fibers were mixed with water and ground, the mass ratio of the short silk fibers to water was 1:5, the grinding time was 6 h, and finally the silk powder with a particle size range of 500-650 mesh was collected and screened by spray drying;

[0034] S12. The silk powder prepared in step S1 is added into water to prepare a silk suspension with a concentration of 10 wt%. The silk suspension is homogenized by high pressure at a homogenization pressure of 80 MPa to obtain a viscous slurry of porous silk powder liquid, which is then filtered and dried to obtain porous silk powder.

[0035] Example 2

[0036] A method for preparing a functional polyester fabric comprises the following steps:

[0037] S1. The polyester fabric is heated in a water bath in a mixed solution of 2.5wt% NaOH and 3wt% ethylenediamine, the water bath temperature is 80°C, the treatment time is 1h, the bath ratio is 1:100, and the polyester fabric is subjected to chemical etching and reduction treatment to obtain a treated polyester fabric;

[0038] S2. A certain amount of porous silk powder was added to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, wherein the mass ratio of the porous silk powder to the nano-TiO2 particles was 10:7, the mass ratio of the silk fibroin to the sodium alginate was 2:2, and the concentration of the viscous aqueous solution of silk fibroin / sodium alginate was 8wt%, and the mixture was stirred sufficiently to allow the surface and interior of the porous silk fibers to fully adsorb the nano-TiO2 particles, and the composite particles were filtered and dried;

[0039] S3. The composite particles are added to a solvent, and then the aniline monomer is added to the composite particle solution, the mass ratio of the composite particles and the aniline monomer is 1:01, and ultrasonic dispersion is performed until the solution is uniform;

[0040] S4. Hydrochloric acid and ammonium persulfate solution were successively added to the homogeneous solution prepared in step S3, the reaction was stirred to obtain a black suspension, which was washed, filtered and dried to obtain silk / TiO2 / polyaniline composite particles;

[0041] S5. Add the composite particles and cross-linking agent prepared in step S4 to the silk peptide solution to prepare a finishing solution, wherein the concentration of the silk peptide in the finishing solution is 18 g / L, and the concentration of the cross-linking agent is 20 g / L. Directly immerse the polyester fabric treated in step S1 in the finishing solution at 90°C for 30 minutes with a bath ratio of 1:50 to obtain the silk powder modified polyester thermal insulation fabric.

[0042] The method for preparing the porous silk powder in step S2 comprises the following steps:

[0043] S11. The undegummed silk fibers were chopped into short silk fibers, and then the short silk fibers were mixed with water and ground, the mass ratio of the short silk fibers to water was 1:10, the grinding time was 2 h, and finally the silk powder with a particle size range of 500-650 mesh was obtained by spray drying and collection and screening;

[0044] S12. The silk powder prepared in step S1 is added into water to prepare a silk suspension with a concentration of 6 wt%. The silk suspension is homogenized by high pressure at a homogenization pressure of 60 MPa to obtain a viscous slurry of porous silk powder liquid, which is then filtered and dried to obtain porous silk powder.

[0045] Example 3

[0046] A method for preparing a functional polyester fabric comprises the following steps:

[0047] S1. The polyester fabric is heated in a water bath in a mixed solution of 1.8wt% NaOH and 3.3wt% ethylenediamine, the water bath temperature is 80°C, the treatment time is 1h, the bath ratio is 1:60, and the polyester fabric is subjected to chemical etching and reduction treatment to obtain a treated polyester fabric;

[0048] S2. A certain amount of porous silk powder was added to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, the mass ratio of porous silk powder to nano-TiO2 particles was 10:5, the mass ratio of silk fibroin to sodium alginate was 2:1.26, the concentration of the viscous aqueous solution of silk fibroin / sodium alginate was 11wt%, and the nano-TiO2 particles were fully adsorbed on the surface and inside of the porous silk fibers by stirring, and the composite particles were filtered and dried;

[0049] S3. The composite particles are added to a solvent, and then the aniline monomer is added to the composite particle solution, the mass ratio of the composite particles and the aniline monomer is 1:1, and ultrasonic dispersion is performed until the solution is uniform;

[0050] S4. Hydrochloric acid and ammonium persulfate solution were successively added to the homogeneous solution prepared in step S3, the reaction was stirred to obtain a black suspension, which was washed, filtered and dried to obtain silk / TiO2 / polyaniline composite particles;

[0051] S5. Add the composite particles and cross-linking agent prepared in step S4 to the silk peptide solution to prepare a finishing solution, wherein the concentration of the silk peptide in the finishing solution is 15 g / L, and the concentration of the cross-linking agent is 15 g / L. Directly immerse the polyester fabric treated in step S1 in the finishing solution at 90°C for 30 min, with a bath ratio of 1:70, to obtain the silk powder-modified polyester thermal insulation fabric.

[0052] The method for preparing the porous silk powder in step S2 comprises the following steps:

[0053] S11. The undegummed silk fibers were chopped into short silk fibers, and then the short silk fibers were mixed with water and ground, the mass ratio of the short silk fibers to water was 1:6, the grinding time was 5 h, and finally the silk powder with a particle size range of 500-650 mesh was obtained by spray drying and collection and screening;

[0054] S12. The silk powder prepared in step S1 is added into water to prepare a silk suspension with a concentration of 8.6 wt%. The silk suspension is treated by high-pressure homogenization at a homogenization pressure of 65 MPa to obtain a viscous slurry of porous silk powder liquid, which is then filtered and dried to obtain porous silk powder.

[0055] Example 4

[0056] A method for preparing a functional polyester fabric comprises the following steps:

[0057] S1. The polyester fabric is heated in a water bath in a mixed solution of 2.2wt% NaOH and 3.6wt% ethylenediamine at a water bath temperature of 75°C for 2h at a bath ratio of 1:80 to chemically etch and reduce the polyester fabric to obtain a treated polyester fabric;

[0058] S2. A certain amount of porous silk powder was added to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, the mass ratio of porous silk powder to nano-TiO2 particles was 10:6, the mass ratio of silk fibroin to sodium alginate was 2:1.6, the concentration of the viscous aqueous solution of silk fibroin / sodium alginate was 9wt%, and the mixture was stirred sufficiently to allow the surface and interior of the porous silk fibers to fully adsorb the nano-TiO2 particles, and the composite particles were filtered and dried to obtain;

[0059] S3. The composite particles are added to a solvent, and then the aniline monomer is added to the composite particle solution, the mass ratio of the composite particles and the aniline monomer is 1:0.9, and ultrasonically dispersed until the solution is uniform;

[0060] S4. Hydrochloric acid and ammonium persulfate solution were successively added to the homogeneous solution prepared in step S3, the reaction was stirred to obtain a black suspension, which was washed, filtered and dried to obtain silk / TiO2 / polyaniline composite particles;

[0061] S5. Add the composite particles and cross-linking agent prepared in step S4 to the silk peptide solution to prepare a finishing solution, wherein the concentration of the silk peptide in the finishing solution is 18 g / L, and the concentration of the cross-linking agent is 18 g / L. Directly immerse the polyester fabric treated in step S1 in the finishing solution at 80°C for 50 min, with a bath ratio of 1:60, to obtain the silk powder-modified polyester thermal insulation fabric.

[0062] The method for preparing the porous silk powder in step S2 comprises the following steps:

[0063] S11. The undegummed silk fibers were chopped into short silk fibers, and then the silk fibers were mixed with water and ground, the mass ratio of silk fibers to water was 1:9, the grinding time was 4 hours, and finally the silk powder with a particle size range of 500-650 mesh was collected and screened by spray drying;

[0064] S12. The silk powder prepared in step S1 is added into water to prepare a silk suspension with a concentration of 7.5 wt%. The silk suspension is treated by high-pressure homogenization at a homogenization pressure of 75 MPa to obtain a viscous slurry of porous silk powder liquid, which is then filtered and dried to obtain porous silk powder.

[0065] Example 5

[0066] A method for preparing a functional polyester fabric comprises the following steps:

[0067] S1. The polyester fabric is heated in a water bath in a mixed solution of 2wt% NaOH and 3.5wt% ethylenediamine, the water bath temperature is 80°C, the treatment time is 1.5h, the bath ratio is 1:50, and the polyester fabric is chemically etched and reduced to obtain a treated polyester fabric;

[0068] S2. A certain amount of porous silk powder was added to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, the mass ratio of porous silk powder to nano-TiO2 particles was 10:5.5, the mass ratio of silk fibroin to sodium alginate was 2:1.4, the concentration of the viscous aqueous solution of silk fibroin / sodium alginate was 10wt%, and the nano-TiO2 particles were fully adsorbed on the surface and inside of the porous silk fibers by stirring, and the composite particles were filtered and dried;

[0069] S3. The composite particles are added to a solvent, and then the aniline monomer is added to the composite particle solution, the mass ratio of the composite particles and the aniline monomer is 1:0.9, and ultrasonically dispersed until the solution is uniform;

[0070] S4. Hydrochloric acid and ammonium persulfate solution were successively added to the homogeneous solution prepared in step S3, the reaction was stirred to obtain a black suspension, which was washed, filtered and dried to obtain silk / TiO2 / polyaniline composite particles;

[0071] S5. Add the composite particles and cross-linking agent prepared in step S4 to the silk peptide solution to prepare a finishing solution, wherein the concentration of the silk peptide in the finishing solution is 20 g / L, and the concentration of the cross-linking agent is 18 g / L. Directly immerse the polyester fabric treated in step S1 in the finishing solution at 85°C for 45 min, with a bath ratio of 1:70, to obtain the silk powder-modified polyester thermal insulation fabric.

[0072] The method for preparing the porous silk powder in step S2 comprises the following steps:

[0073] S11. The undegummed silk fibers were chopped into short silk fibers, and then the silk fibers were mixed with water and ground, the mass ratio of silk fibers to water was 1:8, the grinding time was 4 hours, and finally the silk powder with a particle size range of 500-650 mesh was collected and screened by spray drying;

[0074] S12. The silk powder prepared in step S1 is added into water to prepare a silk suspension with a concentration of 8 wt%. The silk suspension is treated by high-pressure homogenization at a homogenization pressure of 70 MPa to obtain a viscous slurry-like porous silk powder liquid, which is then filtered and dried to obtain a porous silk powder.

[0075] Comparative Example 1

[0076] A method for preparing a functional polyester fabric comprises the following steps:

[0077] S1. The polyester fabric is heated in a water bath in a mixed solution of 2wt% NaOH and 3.5wt% ethylenediamine, the water bath temperature is 80°C, the treatment time is 1.5h, the bath ratio is 1:50, and the polyester fabric is chemically etched and reduced to obtain a treated polyester fabric;

[0078] S2. A certain amount of silk powder was added to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, the mass ratio of porous silk powder to nano-TiO2 particles was 10:5.5, the mass ratio of silk fibroin to sodium alginate was 2:1.4, the concentration of the viscous aqueous solution of silk fibroin / sodium alginate was 10wt%, and the nano-TiO2 particles were fully adsorbed on the surface and inside of the porous silk fibers by stirring, and the composite particles were filtered and dried;

[0079] S3. The composite particles are added to a solvent, and then the aniline monomer is added to the composite particle solution, the mass ratio of the composite particles and the aniline monomer is 1:0.9, and ultrasonically dispersed until the solution is uniform;

[0080] S4. Hydrochloric acid and ammonium persulfate solution were successively added to the homogeneous solution prepared in step S3, the reaction was stirred to obtain a black suspension, which was washed, filtered and dried to obtain silk / TiO2 / polyaniline composite particles;

[0081] S5. Add the composite particles and cross-linking agent prepared in step S4 to the silk peptide solution to prepare a finishing solution, wherein the concentration of the silk peptide in the finishing solution is 20 g / L, and the concentration of the cross-linking agent is 18 g / L. Directly immerse the polyester fabric treated in step S1 in the finishing solution at 85°C for 45 min, with a bath ratio of 1:70, to obtain the silk powder-modified polyester thermal insulation fabric.

[0082] The method for preparing silk powder in step S2 comprises the following steps:

[0083] The undegummed silk fibers were chopped into short silk staple fibers, and then the silk staple fibers were mixed with water and ground. The mass ratio of the silk staple fibers to water was 1:8. The grinding time was 4 hours. Finally, the silk powder with a particle size range of 500-650 mesh was obtained by spray drying, collection and screening.

[0084] Comparative Example 2

[0085] A method for preparing a functional polyester fabric comprises the following steps:

[0086] S1. The polyester fabric is heated in a water bath in a mixed solution of 2.2wt% NaOH and 3.6wt% ethylenediamine at a water bath temperature of 75°C for 2h at a bath ratio of 1:80 to chemically etch and reduce the polyester fabric to obtain a treated polyester fabric;

[0087] S2. A certain amount of porous silk powder was added to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, the mass ratio of porous silk powder to nano-TiO2 particles was 10:6, the mass ratio of silk fibroin to sodium alginate was 2:1.6, the concentration of the viscous aqueous solution of silk fibroin / sodium alginate was 9wt%, and the mixture was stirred sufficiently to allow the surface and interior of the porous silk fibers to fully adsorb the nano-TiO2 particles, and the composite particles were filtered and dried to obtain;

[0088] S3. Add the composite particles and cross-linking agent prepared in step S2 to the silk peptide solution to prepare a finishing solution, wherein the concentration of the silk peptide in the finishing solution is 18 g / L, and the concentration of the cross-linking agent is 18 g / L. Directly immerse the polyester fabric treated in step S1 in the finishing solution at 80°C for 50 min, with a bath ratio of 1:60, to obtain the silk powder-modified polyester thermal insulation fabric.

[0089] The method for preparing the porous silk powder in step S2 comprises the following steps:

[0090] S11. The undegummed silk fibers were chopped into short silk fibers, and then the silk fibers were mixed with water and ground, the mass ratio of silk fibers to water was 1:9, the grinding time was 4 hours, and finally the silk powder with a particle size range of 500-650 mesh was collected and screened by spray drying;

[0091] S12. The silk powder prepared in step S1 is added into water to prepare a silk suspension with a concentration of 7.5 wt%. The silk suspension is treated by high-pressure homogenization at a homogenization pressure of 75 MPa to obtain a viscous slurry of porous silk powder liquid, which is then filtered and dried to obtain porous silk powder.

[0092] Comparative Example 3

[0093] A method for preparing a functional polyester fabric comprises the following steps:

[0094] S1. The polyester fabric is heated in a water bath in a mixed solution of 1.8wt% NaOH and 3.3wt% ethylenediamine, the water bath temperature is 80°C, the treatment time is 1h, the bath ratio is 1:60, and the polyester fabric is subjected to chemical etching and reduction treatment to obtain a treated polyester fabric;

[0095] S2. The undegummed silk fibers were chopped into short silk fibers, and then the short silk fibers were mixed with water and ground, the mass ratio of the short silk fibers to water was 1:6, the grinding time was 5 h, and finally the silk powder with a particle size range of 500-650 mesh was obtained by spray drying and collection and screening;

[0096] S3: adding the silk powder prepared in step S2 into water to prepare a silk suspension with a concentration of 8.6 wt%, subjecting the silk suspension to high-pressure homogenization at a homogenization pressure of 65 MPa to obtain a viscous slurry of porous silk powder liquid, and filtering and drying to obtain porous silk powder;

[0097] S4. Add the porous silk powder and cross-linking agent prepared in step S3 to the silk peptide solution to prepare a finishing solution, wherein the concentration of the silk peptide in the finishing solution is 15 g / L, and the concentration of the cross-linking agent is 15 g / L. Directly immerse the polyester fabric treated in step S1 in the finishing solution at 90°C for 30 min, with a bath ratio of 1:70, to obtain the silk powder-modified polyester thermal insulation fabric.

[0098] The polyester fabric in the embodiment of the present invention is 100D polyester filament woven fabric, plain weave, warp density of 43 strands / cm, weft density of 34 strands / cm, thickness of 0.31mm, and weight of 99.2g / m 2 .

[0099] Test the moisture absorption and heat generation performance of fabrics according to GB / T 29866-2013;

[0100] Test the moisture permeability of fabrics according to GB / T 12704.2-2009;

[0101] The thermal insulation performance of the fabric was tested according to GB / T 11048-2008.

[0102] Maximum temperature rise (°C) Average temperature rise within 30 min (°C) Maximum temperature rise after washing (℃) Example 1 7.8 3.4 7.5 Example 2 8.2 3.5 8.0 Example 3 7.9 3.4 7.5 Example 4 8.3 3.5 8.0 Example 5 8.6 3.6 8.2 Comparative Example 1 4.5 1.8 4.2 Comparative Example 2 7.6 3.4 6.2 Comparative Example 3 6.5 2.7 6.3

[0103] It can be seen from the above table that the fabric developed by the present invention can be used as a heat-generating fabric, but the performance of the silk powder not coated with polyaniline decreases significantly after washing, and some heat-generating particles may fall off during the water absorption process.

[0104] <![CDATA[Water vapor transmission rate (g•m -2 •h -1 )]]> Water evaporation rate (g / h) Example 1 142.56 0.140 Example 2 146.12 0.138 Example 3 143.29 0.136 Example 4 145.91 0.141 Example 5 148.23 0.135 Comparative Example 1 127.25 0.138 Comparative Example 2 150.16 0.140 Comparative Example 3 142.68 0.139

[0105] From the data in the table, it can be found that the moisture permeability of fabrics modified with silk powder without high-pressure homogenization treatment is relatively low. This is because the non-porous knot structure reduces the ability to conduct moisture.

[0106] Warmth retention rate (%) Example 1 34.2 Example 2 35.0 Example 3 34.9 Example 4 34.5 Example 5 35.1 Comparative Example 1 30.1 Comparative Example 2 33.3 Comparative Example 3 32.9

[0107] From the data in the table, we can find that the processed silk powder has a unique pore structure, which increases the air content of the fiber, has a significant warming effect, and thus improves the warmth retention of the fabric.

[0108] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a functional polyester fabric, characterized in that: The following steps are involved: S1. The polyester fabric is heated in a water bath in a mixed solution of NaOH and ethylenediamine, and the polyester fabric is subjected to chemical etching and reduction treatment to obtain a treated polyester fabric; S2. A certain amount of porous silk powder was added to a viscous aqueous solution of silk fibroin / sodium alginate containing nano-TiO2 particles, and the surface and interior of the porous silk fibers were fully adsorbed with nano-TiO2 particles, and the composite particles were filtered and dried to obtain; S3. The composite particles are added to a solvent, and then the aniline monomer is added to the composite particle solution, and ultrasonically dispersed until the solution is uniform; S4. Hydrochloric acid and ammonium persulfate solution were successively added to the homogeneous solution prepared in step S3, the reaction was stirred to obtain a black suspension, which was washed, filtered and dried to obtain silk / TiO2 / polyaniline composite particles; S5. The composite particles and the crosslinking agent prepared in step S4 are added to the silk peptide solution to prepare a finishing solution, and the polyester fabric treated in step S1 is directly immersed in the finishing solution to obtain a silk powder-modified polyester insulation fabric; The method for preparing the porous silk powder in step S2 comprises the following steps: S11. The undegummed silk fibers are chopped into short silk fibers, and then the short silk fibers are mixed with water and ground, and finally the silk powder is collected by spray drying; S12. Add the silk powder prepared in step S1 into water to prepare a silk suspension, subject the silk suspension to high-pressure homogenization to obtain a viscous slurry of porous silk powder liquid, and filter and dry to obtain porous silk powder.

2. The method for preparing the functional polyester fabric according to claim 1, characterized in that: In step S1, the concentration of NaOH is 1.5-2.5wt%, the concentration of ethylenediamine is 3-4wt%, the water bath temperature is 70-80°C, the treatment time is 1-2h, and the bath ratio is 1:50-100.

3. The method for preparing the functional polyester fabric according to claim 1, characterized in that: In the step S11, the mass ratio of the silk staple fibers to water is 1:(5-10); the silk staple fibers and water are ground in a stirring ball mill for 2-6 h.

4. The method for preparing the functional polyester fabric according to claim 1, characterized in that: In step S12, the concentration of the silk suspension is 6-10wt%, and the homogenization pressure is 60-80MPa.

5. The method for preparing the functional polyester fabric according to claim 1, characterized in that: In the step S2, the mass ratio of the porous silk powder to the nano-TiO2 particles is 10:4-7, the mass ratio of the silk fibroin to the sodium alginate is 2:1-2, and the concentration of the silk fibroin / sodium alginate viscous aqueous solution is 8-12wt%.

6. The method for preparing the functional polyester fabric according to claim 1, characterized in that: In the step S3, the mass ratio of the composite particles to the aniline monomer is 1:0.8-1.

Citation Information

Patent Citations

  • Method for preparing anti-ultraviolet polyaniline titanium dioxide conductive fabric

    CN103981719A

  • Silk fibroin / nano material compound and preparation method thereof

    CN114224842A